Kajian Modifikasi Sistem Udara Instrumen Untuk Peningkatan Kehandalan PLTU Indramayu - Eko Sulistyo; Indah Handayasari; Nur Rohman Aziz (JURNAL POWERPLANT, 2014)
Reliable power generation can not be separated from the reliability of the power plant system integration. At the power plant, in particular all the power plant system reliability must be maintained so that no damage is fatal. Especially the instrument air system which is driving tools instrumentation. At indramayu power plant with an installed capacity of 3 x 330 MW nearly all settings instrumentation equipment sourced from compressed instrument air. This system is derived from the rotary screw compressor manifold floaded oil. In the instrument air system contained additional equipment to maintain the quality of the air produced is water dryer. But the fact of compressed instrument air quality is not good and still below the standards of ANSI / ISA-S7.0.01-1996. The output pressure of the compressed air system is also less. Normal operating pressure is 0.75 - 0.8 Mpa, but in actual field conditions of water stress on the receiver tank just 0:57 -0.64 MPa. This happens because of the existing compressor 5 only 3 that stand by. The performance of the compressor that is running downhill. It can be seen from the resulting pressure dropped from 0.85 MPa to 0.76 MPa. Based on these problems required the study and modification of compressed instrument air supply to find the best solution.